A Informática como recurso didático para a aprendizagem de Física no ensino médio - Souza, Gilberto Morel de Paula e (2007)
The accomplishment of this work was motivated by our concerns, while teacher of Physics discipline, in the medium teaching and in the higher education, where we have been observing a lot of difficulties in the students' acting, to the they try to give pursuit out to their studies of the classroom, because of the lack of appropriate equipments, or even, of a laboratory where they can put in practice the studied contents. The work aims at to build and to test an educational software that it serves as tool auxiliadora in Physics learning in the Medium Teaching, in the area of electricity, with emphasis in the study of the electrodynamic in resistors. The developed software comes as an alternative to the learning problems, putting the computer science as auxiliary tool, because, besides being an alternative in the middle of the technological expansion, endowed with several resources, it stimulates the significant learning, according to David Ausubel's perspective. A software containing a program destined to the applicability of physics contents in the branch of the electricity is presented as an auxiliary tool, where the student can, not just, to review the contents presented at room, as well as for in practice, through a virtual laboratory, some of these contents, besides testing their knowledge through a bank of discursive subjects. The evaluation of the developed software was made submitting him/it to the professionals' of physics area appreciation. Equally, through continuous evaluations, they were made comparisons among the students' of five different groups acting, in the same school, that you/they were used of the program as tool of his auxiliary learning, and the acting of those that didn't use it